Pentingnya Pendidikan Demokrasi Untuk Membentuk Sikap dan Prilaku Demokratis - Zahrah, Meza Aulia; Susanti, Emilia; Amalya, Reva Nur; Putri, Yuli Kartika; Istiqomah, Endha; Putri, Andini (Jurnal Pendidikan Kewarganegaraan dan Politik, 2024)
Democracy is very important for the life of the nation and state. Democracy teaches us that the people are the source of power and that they create good rules and protect their rights. However, currently there are many violations of democracy. Many people do not understand democratic attitudes and behavior, which causes inequality. Society is not yet mature enough to follow and respond to the democratic process due to a lack of socialization and education about democracy. The purpose of writing this journal is to provide an understanding of the Importance of Democratic Education to Form Democratic Attitudes and Behavior. This research method uses the library method or literature study. The results obtained show that democratic education has the ability to provide education and help solve the problems of the nation and state. Democratic education instills democratic principles so that it can form a society whose behavior reflects democratic life.